Presenting a Value System Pattern of Female' High School of Secondary High School of Tehran City - karimi, leila; abdollahi, mahbubeh; Nazem, Fatah (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: The value systems play an effective role in improving educational systems, including the education system. Therefore, the purpose of this study was investigating and presenting a value system pattern of female' high schools of secondary high school. Methods: The current research was descriptive from correlation type. The research population were the managers and employees of female' high schools of secondary high school of Tehran city in 2020-21 academic years with number 2934 people, which based on Cochran's formula the sample size was estimated to be 196 people, which this number were selected by purposive sampling method. The research tools were included a demographic information form and a researcher-made questionnaire of value system of high schools (60 questions), which the content validity of the questionnaire was confirmed by the opinion of experts, and its total reliability was calculated with using the Cronbach's alpha method 0.94. After collecting the data with the above tools, they were analyzed by exploratory factor analysis in SPSS and Smart PLS software. Results: The findings showed that the value system of female' high schools of secondary high school had 7 components of self-reliance, universalism and benevolence, success, management, power, security and conformity, and tradition and motivation which the factor load of all of them was higher than 0.50, the average variance extracted of all of them was higher than 0.60 and the reliability of all of them with using Cronbach's alpha method was higher than 0.70. Also, the value system of female' high schools had a direct and significant effect on all seven components of self-reliance, universalism and benevolence, success, management, power, security and conformity, and tradition and motivation (P